Primary prophylaxis to prevent obstetric complications in asymptomatic women with antiphospholipid antibodies: a systematic review. (October 2015) - Amengual, O; Fujita, D; Ota, E; Carmona, L; Oku, K; Sugiura-Ogasawara, M; Murashima, A; Atsumi, T
Objective: Obstetric complications are common in patients with antiphospholipid syndrome. However, the impact of antiphosholipid antibodies (aPL) in the pregnancy outcomes of asymptomatic aPL carriers is uncertain. The aim of this systematic review is to assess whether primary prophylaxis is beneficial to prevent obstetric complications during pregnancy in asymptomatic women positive for aPL who have no history of recurrent pregnancy loss or intrauterine fetal death. Methods: Studies evaluating the effect of prophylactic treatment versus no treatment in asymptomatic pregnant aPL carriers were identified in an electronic database search. Design, population and outcome homogeneity of studies was assessed and meta-analysis was performed. The pooled Mantel–Haenszel relative risk of specific pregnancy outcomes was obtained using random effects models. Heterogeneity was measured with the I 2 statistic. All analyses were conducted using Review Manager 5.3. Results: Data from five studies involving 154 pregnancies were included and three studies were meta-analysed. The risk ratio and 95% confidence interval (CI) of live birth rates, preterm birth, low birth weight and overall pregnancy complications in treated and untreated pregnancies were 1.14 (0.18–7.31); 1.71 (0.32–8.98); 0.98 (0.07–13.54) and 2.15 (0.63–7.33), respectively. Results from the meta-analysis revealed that prophylactic treatment with aspirin is not superior to placebo to prevent pregnancy complications in asymptomatic aPL carriers. Conclusion: This systematic review did not find evidence of the superiority of prophylactic treatment with aspirin compared to placebo or usual care to prevent unfavourable obstetric outcomes in otherwise healthy women with aPL during the first pregnancy.